BENEFITS OF NITRIC OXIDE IN THE MUSCULAR HYPERTROPHY (Fiep Bulletin - online, 2014)
The objective of the present study was to verify the results concerning hypertrophy and muscular strength on individuals submitted to power training during four weeks, from which one group received amino acid supplement, another one received nitric oxide, whereas the last one did not receive any supplementation at all. Six individuals participated in the study, three of them being males and the other three being females. All of them were seemingly healthy and have been practicing weight training for more than a year. The subjects were randomly separated into two groups, three males and three females. Out of the three individuals of each group, one received a nitric oxide supplement, another received amino acid and the third one did not receive any supplement at all. Both groups were submitted to physical evaluation, which included measurements of body mass, height, percentage of body fat and perimeter. The proposed physical activity consisted in resistance training, divided in programs A and B, the exercises being performed three times a week for a whole month. However, prior to start the program, both groups performed a maximum weight test, in order to assess the percentage of weight to be used in the training programs. The results showed there was a gain of power and muscle mass as well as a reduction of body fat in the female group, making evident the better results obtained with those individuals which received a nitric oxide supplementation. On the other hand, all the male subjects showed body fat reduction, but only those which did not receive any supplement at all failed to show any gain of power. Concerning gain of body mass, only that individual that received a nitric oxide supplementation did succeed.This study showed, therefore, that, despite the small number of participants, there were significant percentage variations with respect to anthropometric parameters among the individuals, thus revealing that a nitric oxide supplementation was effective in increasing power and muscular hypertrophy.
Keywords: hypertrophy; nitric oxide; power